Perceived Empowerment, Social Support, and Quality of Life Among Chinese Older Residents in Long-Term Care Facilities. (December 2018) - Wang, Jing; Wang, Junqiao; Cao, Yuling; Jia, Shoumei; Wu, Bei
Objective: This study examines how older residents' social support and perceived empowerment are associated with their quality of life (QOL) in long-term care (LTC) facilities in Shanghai, China, controlling for their health-related conditions, facility type, and other socio-demographic characteristics.Method: Using a convenient sampling approach, we selected nine LTC facilities in Shanghai, China. We surveyed 515 older residents from these facilities.Results: Older participants in this study rate their QOL, social support, and perceived empowerment as moderate, and these variables are positively associated with their QOL. Older residents who live in government-owned and private-run LTC facilities are more likely to have a higher level of perceived QOL compared with those living in government-run facilities.Discussion: There is an urgent need to increase staff awareness and capacity to empower older residents, and to engage them in their care plan and delivery. LTC facilities could provide more opportunities for older residents' social networking within and outside LTC facilities. Improvement of older residents' QOL is critical in the future development of resident-centered care models in LTC facilities.